2016
DOI: 10.1016/j.trim.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Added effects of dexamethasone and mesenchymal stem cells on early Natural Killer cell activation

Abstract: Graft rejection and graft-versus-host disease are leading causes of transplant related mortality despite advancements in immunosuppressive therapy. Mesenchymal stem cells (MSCs) offer a promising addition to immunosuppressive drugs (ISD), while NK-cells are increasingly used as effector cells in graft-versus-leukemia. Combined therapy of ISD, NK-cells and/or MSCs is used in clinical practice. Here, we examined the effects of MSCs and selected ISD (tacrolimus, cyclosporin A, mycophenolic acid, dexamethasone) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…Inhaled corticosteroids (ICS) are potent immunomodulators and high doses of ICS are routinely administered in response to COPD exacerbations. Indeed, high doses of ICS use has been shown, both in vivo and in vitro, to be associated with alterations to NK surface phenotype and function 10,11 . Therefore, patients with an exacerbation and possible ICS use in the month prior to enrollment were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Inhaled corticosteroids (ICS) are potent immunomodulators and high doses of ICS are routinely administered in response to COPD exacerbations. Indeed, high doses of ICS use has been shown, both in vivo and in vitro, to be associated with alterations to NK surface phenotype and function 10,11 . Therefore, patients with an exacerbation and possible ICS use in the month prior to enrollment were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is evidence that steroid treatment may have a beneficial effect on MSC function as well. Dexamethasone treated MSCs suppress IFN-γ, perforin, and CD69 expression in NK cell populations (48). In addition, we have previously shown that loading MSCs with intracellular microparticles containing budesonide enhances their suppression of peripheral blood mononuclear cells (PBMCs) (2).…”
Section: Discussionmentioning
confidence: 99%
“…ELISA results revealed that HFC treatment significantly increased the secretion of PGE2 in BMSCs compared with that by untreated BMSCs, which was antagonized by NS-398, a specific inhibitor of COX-2, which is responsible for PGE2 production (Fig. 6A) (30). EP4 is the receptor for PGE2, an important transmembrane G protein-coupled receptor in macrophages (31).…”
Section: Expression Of Genes Associated With Inflammation In Raw2647mentioning
confidence: 98%